Multi-Stakeholder Synergy in Innovation-Based Regional Development Planning at the Regional Development Planning Agency of Sidoarjo Regency - Jhoni Arwan S; Ika Devy Prmudiana; Amirul Mustofa (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
This study analyzes multi-stakeholder collaboration in innovation-based regional development planning at the Regional Development Planning Agency (Bappeda) of Sidoarjo Regency, emphasizing institutional mechanisms, data integration and digital innovation, joint financing schemes, and actor capacity and participation dynamics. The research focuses on the need to improve the effectiveness of development planning through planned, participatory, and data-driven intersectoral collaboration. Applying a qualitative case study approach, information was collected through in-depth interviews, participant observation, and analysis of planning documents. It was then analyzed using data reduction, thematic grouping, and source triangulation techniques. The research findings indicate that institutional synergy has been realized through formal forums such as development planning meetings and group discussions. However, coordination remains suboptimal due to overlapping roles between regional government agencies and the lack of a sustainable collaborative mechanism. Digital data integration still faces challenges due to limited platform content and user technical capabilities, resulting in data utilization not fully supporting evidence-based decisions. In terms of financing, collaborative schemes have begun to be implemented but are inconsistent, particularly in combining funding sources from various sectors. The capabilities of actors show striking differences, which impact the quality of public engagement and the efficiency of facilitating the planning process. Overall, these results confirm that the effectiveness of innovative planning is largely determined by the integration of digital systems, strengthening collaboration between stakeholders, and enhancing institutional capacity. This study suggests designing a more organized, interactive, and long-term multi-actor synergy model.